Distribusi Chemical di Finishing Line PT. XYZ - Danny Fernando; I Gede Agus Widyadana (Jurnal Titra, 2017)
PT. XYZ is a company that produces shoe. This study is subjected to reduce expired chemicals because it was keep too long in finishing line and to design a safer and ergonomic trolley. The amount of expired chemical due to there is no standard scheduled for distributors to distribute chemical in the finishing line so that many chemicals are stored in line and finally expired. The trolley is now considered less secure because there is no buffer on the front of the trolley thus allowing the jerry can to fall. Chemical distribution schedule will be made based on work measurement method. The result of this work measurement is that chemicals will be distributed for an hour so that distributors will distribute chemicals seven times in one work shift. The number of chemicals allowed to be in the finishing line is also limited by the need for chemical for one hour so that no chemical is wasted due to expired. The new trolley will be made based on anthropometry data to make it more comfortable and safe to use.